Atividade inseticida de extratos vegetais sobre Gyropsylla spegazziniana (Lizer & Trelles, 1917) (Hemíptera: Psyllidae) - Barzotto, Ionete Lucia Milani (2010)
The Paraguay tea (Ilex paraguariensis) is a plant of economic importance to Brazil, mainly to the southern states, where most production and consumption. The leaves are industrialized aiming at preparing tea, mate, soluble powder, and the obtaining of active pharmaceuticals and cosmetics. The Gyropsylla spegazziniana (Hemíptera: Psyllidae) is considered a pest of Paraguay tea, since it causes hypertrophy of new leaves, giving rise to a symptom known as "Paraguay tea bulb , a structure that houses the nymphs, which feed this site until close to adulthood. The damaged leaves usually fall and reduce crop yield. As the Paraguay tea is consumed practically 'in natura', the use of chemicals is not recommended. The use of insecticidal plants is an alternative for pest control of this culture as it does not pose risks to the environment or to humans. The objective of this study was to test the efficiency of extracts of Eucalyptus spp., Azadirachta indica, Melia azedarach, Cymbopogon citratus, Chrysanthemum spp, Trichilia pallida, Leucaena leucocephala, Chenopodium ambrosioides and Annona squamosa for the control of G. spegazziniana in laboratory conditions. In order to do an initial screening were tested ethanol extracts of 25% aqueous to 20%, and a commercial product based on neem seed (Organic Neem ®), 10%, and selected the ones that caused at least 50 % mortality. The control does not receive any treatment. The extracts were sprayed prior and subsequent to infestation of insects on test plants or twigs of Paraguay tea. In the first stage, the only effective treatment in prior spray was 20% aqueous extract of Chrysanthemum spp (85%). The alcoholic extracts of 25%, using the same method showed better results: A. squamosa (93.6%), T. pallida (90.4%), C. citratus (58.2%), Eucalyptus spp (51.6%) and M. azedarach (64.5%). In the method of spraying later, Eucalyptus spp, and M. azedarach aqueous, with 77.7% and 70.5% respectively, showed potential for insect control. L. leucocephala (100%), Chrysanthemum spp 85.5%), C. citratus (55.5%), A. squamosa (51.6%), C. ambrosioides (55.5%) alcoholics were more effective. After dilution to 10%, only the extract of C. citratus alcoholic and the commercial product, with the method of spraying later showed potential insecticidal, with a mortality rate above 50%.